Treatment Standards and Individualized Therapy of Myasthenia Gravis - Paul Urban, Peter; Jacobi, Christian; Jander, Sebastian (Neurology International Open, 2018)
A wide range of established treatment options is currently available for myasthenia gravis. These include cholinesterase inhibitors for symptomatic treatment and a broad spectrum of immunosuppressive, immunomodulating or cell-depleting options to modify the underlying immunological process. Appropriate use allows the great majority of patients to lead a normal life. Specialized centers integrating outpatient and in-hospital resources as well as interdisciplinary competences offer important advantages for optimum individualized therapy.
Keywords: myasthenia gravis; neuromuscular disorder; treatment